Clinical pattern and burden of strabismus in a teaching institute of Northeast India - Tanie Natung; Oinam S. Devi; Lanalyn Thangkhiew; Subhankar Paul (Journal of Family Medicine and Primary Care)
Purpose: To determine the clinical pattern and burden of strabismus in a teaching institute of Northeast (NE) India. Methods: In this hospital-based, cross-sectional study, detailed clinical evaluation of patients with manifest strabismus was carried out for a period of one and half years. Results: Out of the 7222 new outpatient department attendances, a total of 110 new patients with manifest strabismus were found, with a hospital-based burden of 1.52% [95% confidence interval: 1.3–1.8]. Comitant strabismus was seen in 84.55%, and incomitant in 15.45%. Exotropia comprised 70%, esotropia 26.36%, hypertropia 10%, and hypotropia 2.72%. The angle of deviation was large in most of the participants (69.09%) with a mean of 34.90 ± 17.08 PD for horizontal and 13.29 ± 8.97 PD for vertical deviations. A cause of strabismus could be identified in 30.91%. Paralytic strabismus was seen in 15.45%, sensory in 11.82%, infantile in 1.82%, and accommodative in 1.82%. Amblyopia was found in 5.45%. In our study, 25.45% patients underwent strabismus surgery, while 74.55% patients either needed conservative management or were being worked up for surgery till the end of this study. Conclusion: This study determined the pattern and burden of strabismus in a teaching institute of NE India. Since the institute caters to patients from different states of NE India, this study gives an indirect picture of the burden of strabismus of the whole of NE India. It is hoped that these data will aid in determining the overall burden of strabismus in the country. They will also help the family medicine and primary care physicians to have an idea about the burden and pattern of strabismus in the community, thus enabling them to create awareness about strabismus, remove the undue apprehensions of patients, and do timely referrals for treatment and prevent irreversible visual loss.